The affected factors of loss to follow up (LFU) among HIV patients with antiretroviral therapy (ART) in Dr. Sardjito General Hospital, Yogyakarta, Indonesia - Sri Purwaningsih; Yanri Wijayanti Subronto; Erna Kristin (Indonesian Journal of Pharmacology and Therapy, 2020)
HIV infection is a global issue which is related to the increasing cases of HIV and AIDS in various countries including in Indonesia. Antiretroviral therapy (ART) that addressed for reducing the virus proliferation is not always followed by good medication adherence among patients. The ART loss to follow up (LFU) is a common problem in Indonesia. However, information concerning the affected factors of LFU among HIV patients with ART is limited. This study aimed to investigate the affected factors of LFU among HIV patients in the early two years of ART. A retrospective cohort study was conducted in Dr. Sardjito General Hospital, Yogyakarta among 369 medical records of HIV patients that met the inclusion and exclusion criteria. The inclusion criteria were HIV patients who started ART in January 2008 to December 2012, aged > 17 years with a complete medical records. The data of sociodemography and medical status patients were obtained from medical record, ART, and pharmacy register of the patients. Patient characteristics observed in this study included demographic factors such as age, sex, residence, education level, risk factors, and also medical status factors such as clinical stage, tuberculosis (TB) co-infection, functional status, and CD4 cell counts. The data were analyzed using Kaplan Meier and Cox Proportional Hazard. The results showed that patients with TB co-infection in early therapy and working functional status were significant factors of LFU (p<0.05). Patients without TB co-infection were half as much protected from LFU compared to patients with TB infection (HR=0.50; 96%CI: 0.34-0.75). It can be concluded that TB coinfection in early therapy and working fuctional status are the significant factors that influenced the LFU incidents in the two years of early therapy.